Mobile service desk: integrando sensibilidade ao contexto e sistema de recomendação - Oliveira, Taciano Balardin de (2013)
The management of problems occurred in environments that make use of Information Technology (IT), coupled with the need for a rapid response support teams, makes organizations require systems to manage these incidents. The Service Desk presents itself as a good solution to centralize these records. Concepts based computing context, recommender systems, mobile computing can enhance these applications. Therefore, the aim of this work is to design and implement a system of Service Desk Mobile, called Mobile Service Desk (MSD), which adds context awareness features such as user location, technical experience and temporal context. Moreover, the tool is integrated into a recommendation system, which stores past interactions and suggests as a possible solution for new similar incidents occurring in the managed environment. As contributions of this work, in addition to system design that aims to reduce unnecessary time-shift and optimize the allocation of technical, algorithms were compared for similarity analysis and applied to NBR 9241-11 for usability evaluation of some products Service Desk.